GROWTH AND BLOOD PROFILE OF CORAL TROUT GROUPER Plectropomus leopardus SEEDS IN DIFFERENT SALINITIES - Ketut Maha Setiawati; Ketut Mahardika; A. A. Ketut Alit; Daniar Kusumawati; Indah Mastuti (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
The information about the optimum and tolerable salinity to support in the success of coral trout grouper’s seed culture is still limited until now. The aim of this study was to understand the effect of different salinity on growth, survival, feed conversion (FCR) and the profile of blood (hematocrit and hemoglobin) of coral trout grouper seed. The seed with total length 6.0 ± 0.5 cm and body weight 3.2±0.3 g were used as tested animals. Five different salinity treatments, namely: 10±1 ppt (A), 16±1 ppt (B), 22±1 ppt (C), 28±1 ppt (D), and the sea water (34 ppt) as a control (E) were undertaken in this study, with three replications for each treatment. Salinity values were reach by adding freshwater into the tested seawater. Water changing system in this study was performed in recirculation process, with 25% of water replacement every 7 days. The result of this study showed that the survival rate values were 100% for all treatments, indicating that coral trout grouper seed can be cultured in the range of salinity between 10 to 34 ppt.  The highest total length and body weight were recorded from treatment C (22 ppt), as well as noted to gain the lowest FCR. Correspondingly, the seed in treatment C also founded to have in the greatest amount of hematocrit and hemoglobin. Optimum salinity for rearing of coral trout grouper seeds  with  total length 6 cm was 22 ppt.  Keywords: salinity, growth, survival rate, feed conversion, blood profile